Pengaruh Green Marketing, Brand Awareness, Dan Harga Terhadap Keputusan Pembelian Konsumen Generasi Z Tas Ecobag Di Indomaret - Kuncahyo, Angger; Rachma, N.; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study's goal is to comprehend and investigate how consumers at Indomaret make decisions about the purchase of Ecobag bags (Y) in relation to Green Marketing (X1), Brand Awareness (X2), and price (X3). The quantitative approach is the research method used. Purposive sampling is the sampling technique employed, and there were 90 participants in all. Students from generation Z living in the Lowokwaru District participated in this study. Using SPSS software version 25, multiple linear regression analysis was the data analysis technique employed in this investigation. The study's findings suggest that pricing, brand awareness, and green marketing all significantly affect consumers' decisions to buy. Purchasing decisions are significantly influenced by brand awareness and green marketing. Price, however, has little bearing on what people decide to buy Keywords: Green Marketing, Brand Awareness, Price, Purchase Decision